A novel lymph node staging system for gastric cancer including modified Union for cancer Control/American Joint Committee on cancer and Japanese Gastric Cancer Association criteria. Issue 10 (October 2020) - Gong, Yingbo; Pan, Siwei; Wang, Xin; Zhu, Guolian; Xu, Huimian; Zhu, Zhi
Abstract: Background: The TNM system of the International Union for Cancer Control/American Joint Committee on Cancer (UICC/AJCC) and the Japanese Gastric Cancer Association (JGCA) systems are the most used lymph node (LN) staging systems in gastric cancer. This study estimated the influence of anatomic location-based node stations on survival and proposed a new staging method based on both the number and anatomical distribution of metastatic LNs (mLNs). Methods: Stage I–III gastric cancer patients with radical gastrectomy were retrospectively evaluated. Overall survival (OS) was estimated in 1786 patients with UICC/AJCC stage N1–N3b disease and compared with estimates obtained using JGCA group 1–3 mLN staging. Results: The OS of UICC/AJCC stage N1–N3b patients with group 2 JGCA mLNs was significantly worse than that of patients with only group 1 mLNs. The OS of the patients with group 2 mLNs was similar to that of patients with group 1 mLNs but in the next more advanced UICC/AJCC-N stage. The OS of patients with group 3 mLNs was worse than that of patients with any UICC/AJCC-N stage and was similar to that of N3b patients with group 2 mLNs. A new pathological node (pN) staging classification was developed that advanced the N-staging of patients with group 2 mLNs. It was a better indicator of prognosis than the eighth UICC/AJCC-N and the thirteenth JGCA group staging systems. Conclusions: A simple, accurate pN staging system including both the number and location of mLNs had improved homogeneity, discriminatory ability, and gradient monotonicity.